Focus Ultrasound‐Induced Blood‐Brain Barrier opening enhances anti‐pGlu3 Aβ mAb delivery and amyloid‐beta plaque clearance. (31st December 2021) - Bathini, Praveen; Sun, Tao; Shi, Qiaoqiao; Zhang, Yongzhi; Taudte, Nadine; Schenk, Mathias; Hettmann, Thore; Schilling, Stephan; McDannold, Nathan; Lemere, Cynthia A
Abstract: Background: Alzheimer's Disease (AD) is a neurodegenerative disorder characterized by the accumulation of amyloid plaques and hyperphosphorylated tau in the brain. Currently, therapeutic agents targeting amyloid appear promising for AD, however, delivery to the CNS is limited due to the blood‐brain‐barrier (BBB). Focused ultrasound (FUS) is a method to induce a temporary opening of the BBB to enhance delivery of therapeutic agents to CNS. Our lab has shown that an mAb (07/2a), targeting N‐terminally truncated and modified toxic Aβ species, reduced pGlu3 Aβ and general Aβ cerebral plaques in aged APP/PS1dE9 mice. Here, we asked whether FUS‐induced BBB opening enhances the delivery of 07/2a mAb and whether it has any additive effect on cognition or plaque clearance. Methods: First, 24 mo‐old APP/PS1dE9 mice were i.v. infused with a single dose of 300 µg 07/2a with or without hippocampal FUS sonication (n=5/group) with i.v. infused Optison microbubbles and euthanized 4 or 72 h later; brain levels of antibodies were measured by ELISA. Next, 16 mo‐old APP/PS1dE9 mice were treated weekly for 3 weeks with PBS (n=9), 500 µg 07/2a alone (n=9), FUS alone (n=7) or 07/2a + FUS combination (n=6). Behavioral testing in the Water T Maze (WTM) was performed 1‐2 weeks later followed by euthanasia. Results: FUS treatment increased 07/2a mAb levels in brain by 5.9‐fold 4 hr (41.7 pg/mg for mAb alone, vs. 244 pg/mg mAb+FUS; t=3.48, p<0.005) and 5.5‐fold (mean=31.5 pg/mg for mAb alone, vs. 173 pg/mg for mAb+FUS; t=2.9, p<0.05) 72 hr post‐treatment. Immunohistochemistry confirmed a significant increase in IgG2a mAb staining in the mAb+FUS treated mice at 4 hr (p=0.007) and a strong trend in the mAb+FUS treated mice at 72 hr after treatment compared to mAb alone. Three weekly treatments of 07/2a improved cognition however, when combined with FUS, this improvement occurred faster and in a higher percentage of mice and led to reduced hippocampal plaque load compared to PBS control mice. Conclusions: Transient opening of the BBB by FUS increased 07/2a delivery to the brain, improved cognition, and enhanced Ab clearance in aged APP/PS1dE9 mice, suggesting that FUS increased efficacy of the 07/2a mAb.